Liver metastasis mimicking a liver cyst of a thymoma in a 38-year-old immunocompromised patient - Petzold, Golo; Ströbel, Philipp; Seif Amir Hosseini, Ali; Ellenrieder, Volker; Neesse, Albrecht (Zeitschrift für Gastroenterologie, 2021)
Cystic liver lesions (CLL) are common and, in the majority of cases, benign. However, the range of differential diagnoses of CLL is wide. A combination of medical history, blood test results, and imaging can help find the correct diagnosis. We report the case of a 38-year-old immunocompromised female patient with a history of thymectomy and postoperative radiation 3 years prior due to thymoma. Subsequently, the patient was referred to our department for clarification of a cystic liver lesion. During short-term follow-up, the lesion increased in size, and due to the contrast agent behavior in the ultrasound and MRI examination, the suspicion of a biliary cystadenocarcinoma was considered.Furthermore, imaging showed several subcentimetric liver lesions of unknown dignity. Finally, pericystectomy and atypical partial liver resection was performed. Histology revealed a cystic metastasis of the malignant B3 thymoma and a cavernous hemangioma. Liver metastases of a thymoma are rare, and this is the first case of a cystic liver metastasis of a thymoma. The presented case illustrates that in the management of CLLs beside imaging techniques, the medical history with previous conditions should be considered, especially in past malignancies.
Keywords: Zystische Leberläsion; Zyste; Biliäres Zystadenokarzinom; Thymom; Lebermetastasen